A Production systems study of Jamaica Packaging Corporation - Chico, Reynaldo Paul B. (College of Engineering, 2004)
After several plant visits and discussions regarding collected data and observations, the group concluded that immediate problems present in the plant covered areas in plant layouting, production forecasting, capacity planning and quality control. Problems regarding working conditions in the plant were also observed by the group. With the cause and effect diagrams, these identified problems were analyzed and given proposed solutions. The present layout of Jamaica Packaging Corporation (JPC) cannot be considered as optimal since machine locations are improper for continuous production flow (see plant layout). Due to this constraint, workers and materials have to travel extra distance from one workplace to another resulting in production time losses. Lack of an effective waste disposal system and the need for inventory storage contributes to the facility's disorganized layout. The proposed plant layout assumes other machines, e.g. creaser - machine which makes lines in the boardsheets by folding and pressing, partitioner - machines which divides the boardsheets into the component parts of the box, can be transferred for a better production flow. The group also learned that there is no existing forecasting method being used in the Production and Planning control Department (PPC). This is due to the indiscriminate acceptance of job orders in the Marketing Department. At present JPC accepts all orders ranging from ten pieces and above. Moreover, use of irregular lead times because of frequent rush orders have prevented the PPC staff from having a forecasting model. This lack resulted in scheduling problems and irregular production, among others. What the group suggested was the use of demand management. JPC can offer discounts to customers who can inform them beforehand of their orders. This will result in the smoothening of the irregularities in demand. When demand is more or less regular, the forecasting model can be developed and the study has presented one such model. The inadequacy of capacity planning is also a major concern. The Marketing Department accepts orders without considering plant capacity. Poor coordination between these two departments can be improved by setting machine capacities. The Marketing Department can reject rush orders that will contribute to excess demands with regards to the standard already set. Inefficient planning results in too much wastages. This is due to indiscriminate cutting of paper rolls without studying which optimal cut can be used. The study presents a linear programming model on the determination of the optimal cut given the number and size of the output needed. The group also noticed that quality control checks are inadequate. The company has quality control policies but the Quality Control Department does not follow these. Regular quality checks following the standard guidelines presented in the study can eliminate the poor quality of some boxes. Other problems that the group observed were poor lighting conditions, flood during rains, dirty workplace, and high temperature inside the plant. Few lights were installed inside the plant resulting in poor visibility. This increases the possibility of accidents and below standard products. Additional lights can solve this problem. Floods during rains can stop production and spoil the finished products. A general patch-up of the roofs and an overall cleaning of the drainage system can eliminate the threat of floods. Waste disposal problems clutter up in the working area making motion difficult.Putting waste boxes in key points along the working area and better coordination between the Waste and Production Department will result in a cleaner work environment. Lastly temperatures of 35-38 degrees Celsius were observed inside the area, Inefficient production and the health risks posed to the workers are the notable effects of the heat. Blowers and exhaust fans should be installed around the work area particularly in the places near the boiler.